PENGEMBANGAN ATRAKSI WISATA PANTAI TANJUNG KARANG SEBAGAI KAWASAN WISATA BAHARI DI KABUPATEN DONGGALA - Widodo, Eko (Katalogis, 2017)
This study aims to: (1) identify potential physical and socio-economic Â Tanjung Karang Beach which can be developed for tourist attractions nautical, Â (2) to identify the perception of tourists to marine tourism in the Area Tourism Tanjung Karang, (3) to analyze the development strategy of the tourist attractions in Region travel Tanjung Karang traveler perception, (4) to analyze the impact of the development of tourist attractions, the economic development in the area of Cape Coral travel. The study found that the potency of physical and socio-economic in Area Tourism Tanjung Karang well and increased perception wisatawanpun well against Marine Tourism in Region Tourism Tanjung Karang, resulting in a SWOT analysis to analyze the development strategy attractions Tanjung Karang is located in Quadrant 1, which means that Tanjung Karang fully able to overcome the existing weaknesses by using its power to develop tourist attractions. This impact both on economic development in Tanjung Karang Beach Tourism Region, by improving the quality of the local environment and is also expected to increase the number of tourists who come to visit in Tanjung Karang so as to encourage the regional economy in Donggala district. Increased regional economy will provide job opportunities in the field of business travel services and generate income through the development tax and entry fees to Cape Coral Coast marine tourism.